Research of psycho-emotional stability in the basal emotions matrix - Vyacheslav T. Volov; Vsevolod V. Volov (Национальный психологический журнал, 2016)
The paper presents the analysis of psycho-emotional state estimation, which is based on the facial feedback monitoring. The myographic research data revealed qualitative and quantitative singularities of epileptics on the range of basal emotion indicators which have been received on the matrix method way basis and model of quality diagnostics. For the calibration method the study involved healthy subjects. Beforehand myographic cards were developed to measure the tone of facial muscles during the trial of six basal emotions. The experiment was arranged in such a way as to reflect the work of reverse afferentation emotions. Ahe amplitude-frequency characteristics of the samples and emotional reactions of involuntary reactions were identical. Therefore samples of complementary development of natural emotions were tried: the first test stage included efferent synthesis, the second stage used afferent synthesis. Defining features of emotional response was carried out on the basis of the model of quality diagnostics of emotions. The chiral effects were identified: mimic pattern emotions in both samples. This effect allowed to separate violations of the personal response from the specific pattern, which blocks the effects of restrictions and other emotions. The matrix method allowed to produce quantitative estimates of mental and emotional state on the basis of instrumental measurements of basal emotions. In the group of epileptics, on the facial expression level emotional blocks are identified which are connected with ceral effects (repented characteristic deviation of emotional patterns in the two probes). Additionally differences on quantitative estimations between the epileptics reactions and healthy individuals are revealed.